(untitled) (Coventry Open Press, 2025)
As potentially the most disruptive technology since the invention of writing, the printing press, or the internet, Artificial Intelligence (AI1) could lead to deep transformative changes in human psychology, religious beliefs and practices, power and economic structures, and hence impact societal cohesion, personal and cultural resilience. As such it demands rigorous academic scrutiny of its applications and impacts across a range of areas. This literature review is the first output of a SALIENT Hub-funded project that explores the deep and complex intersection of religion, artificial intelligence (AI), culture and societal resilience. It examines the psychological and spiritual impacts of AI, surveys theological and philosophical engagements across major world religions, and analyses the ways in which faith organisations are beginning to adopt, or reject, generative and agentic AI in their day-to-day practices. It examines the relationship between culture, societal resilience and the vital role played by faith, and ends with a discussion of religious parallels in AI narratives and the possibility of AI generating new religious belief systems or emerging as the basis of a new religion itself. By situating these developments within broader frameworks of societal resilience and cultural adaptation, the review highlights how religious traditions both interrogate and integrate generative and agentic AI, offering critical insights into the ethical and existential dimensions of technological transformation.